Photic entrainment of the mammalian rhythm in melatonin production - Illnerová, H; Sumová, A (Journal of biological rhythms, 1997)
This review summarizes studies on the photic entrainment of the circadian rhythm in the rat pineal melatonin production, namely of the rhythm in N-acetyltransferase (NAT) activity, and compares the NAT rhythm resetting with preliminary results on the resetting of an intrinsic rhythmicity in the suprachiasmatic nucleus (SCN) of the hypothalamus, namely with the entrainment of the rhythm in the light-induced c-fos gene expression. Phase delaying of the NAT rhythm after various light stimuli proceeds within 1 day with almost no transients, whereas during phase advancing of the rhythm only the morning NAT decline is phase advanced within 1 day and the evening rise phase shifts through transients. A light stimulus encompassing the middle of the night may phase delay the evening NAT rise, phase advance the morning decline, compress the rhythm waveform, and eventually lower its amplitude. Similarly, a long photoperiod compresses the NAT rhythm waveform. The magnitude of phase shifts of the NAT rhythm, as well as their direction, depends on a previous photoperiod. Phase shifts of the evening rise in c-fos gene photoinduction in the SCN and of the morning decline are similar to those of the pineal NAT rhythm after all light stimuli studied so far. The data indicate that the resetting of the rhythm in melatonin production in the rat pineal gland reflects changes in the SCN functional state and suggest that the underlying SCN pacemaking system is complex.
Keywords: Melatonin; krysa rodu Rattus; Photoperiod; fotoperioda; Animals; lidé; světelná stimulace; Periodicity; Photic Stimulation; melatonin; periodicita; zvířata; Humans; Rats